POTENSI LIMBAH TANGKAI BUAH CABAI RAWIT DAN CABAI MERAH KERITING SEBAGAI BIOINSEKTISIDA NYAMUK Aedes aegypti: POTENTIAL OF BIRD'S EYE CHILI AND RED CURLY CHILI STEM WASTE AS A BIOINSECTICIDE FOR Aedes aegypti - Fadilla Amelia Riski; Dwi Susanti; Mastuti Widianingsih (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2026)
Abstract The stems of bird's eye chili (Capsicum frutescens L.) and curly red chili (Capsicum annuum L.), which are typically considered waste, actually hold compounds with potential for biological activity. Phytochemical screening has shown that stems of bird’s eye chili contain secondary metabolites such as alkaloids, phenolics, tannins, flavonoids, terpenoids, and saponins, while curly red chili stems contain alkaloids, steroids, phenolics, tannins, flavonoids, and saponins. The objective of this research to evaluate the effectiveness and determine the optimal concentration of both extracts as bioinsecticides against Aedes aegypti mosquitoes. Extraction was performed by maceration using 96% ethanol (ratio simplicial:solvent=1:10). The yield of bird’s eye chili extract was 7.45%, while curly red chili extract of 8.06%. The experiment consisted of five treatment groups with extract concentrations of 1%, 3%, and 5%; transfluthrin as a positive control; and distilled water as a negative control. Each group contained 25 Aedes aegypti mosquitoes. Mortality result indicated that both extracts had bioinsecticidal activity, although their effectiveness varied at different concentrations. The stems of bird’s eye chili extract showed the greatest effect at 5% concentration, with an LC₅₀ value of 4,177% at the 4th hour, while the curly red chili stems extract was most effective at 5% concentration, with an LC₅₀ value of 4,048% at the 5th hour. In conclusion, chili stem waste extracts demonstrate promising potential as effective and environmentally friendly botanical bioinsecticides for controlling Aedes aegypti. Keywords: Aedes aegypti, Bioinsecticide, Curly Red Chili, Chili Stem Waste